Spurs and sparks - Hedlund, Jody (A Healing Springs Ranch novel, 2025)
"Tyler McQuaid has been too busy managing his family's luxury ranch resort to think about love. But when his dad gets sick and may not have long to live, Tyler begins to question what is truly important. He's already failed once at love and marriage, but how can he say no to his dad's sickbed wish that he try again? Kinsey Wingrove, a traveling nurse, prefers to keep her relationships short and sweet, and yes, even shallow. With the losses she's already experienced in life, it's just easier that way. When she arrives at Healing Springs Ranch, she clashes with her new patient's son, the handsome cowboy who runs the place and doesn't think she's the right nurse for his dad. As sparks fly between Tyler and Kinsey, the meddling, matchmaking McQuaid family sees that more can exist between the two than they will acknowledge. Can Tyler accept and move beyond the mistakes of his past to allow for the McQuaid legacy of love -- a fast, furious, and forever kind of love? Or will he let Kinsey's fears push him away forever?"--